Factors Determining Consumer Acceptance of Biofortified Food: Case of Zinc-Fortified Wheat in Pakistan's Punjab Province - Rizwan, Muhammad; Zhu, Yueji; Qing, Ping; Zhang, Debin; Ahmed, Umar I.; Xu, Hui; Iqbal, Muhammad A.; Saboor, Abdul; Malik, Arshad M.; Nazir, Adnan; Wu, Xuelian; He, Puming; et al. (Frontiers in Nutrition, 2021)
Zinc (Zn) is a fundamental micronutrient required by all living organisms. Zn deficiency among children under five years, pregnant, and child-bearing women has been identified in developing countries such as Pakistan. Biofortified crops can increase micronutrient levels and decrease deficiencies. Meanwhile, consumer acceptance is essential, given that genetic alterations can occur during the process of biofortification, resulting the changes in sensory traits and the quality of grains. Therefore, the present study focuses on the determining factors for consumer acceptance of Zn biofortified wheat. To achieve the objective of the study, an experimental survey was conducted, qualitative and quantitative data were collected and analyzed from 203 respondents in the Punjab province. The results regarding sensory perceptions revealed that people attached great importance to the appearance of the chapati prepared with Zn biofortified wheat. They were willing to purchase Zn biofortified wheat when they were asked to make a choice between the conventional wheat and the Zn biofortified wheat. Moreover, the probit model illustrates that the level of education in the family and having young children aged under five years in the household had a positive impact on the acceptance of Zn biofortified wheat among the participants. The findings suggest that there is significant scope for promoting Zn biofortified wheat in the country. It is also imperative to ensure its availability across various regions at a subsidized price, so that households with weak purchasing power can buy and address their Zn deficiency. Policy makers could introduce reforms targeting business communities for food management, keeping Zn biofortified wheat in the priority stream.